2018
DOI: 10.1176/appi.ps.201700344
|View full text |Cite
|
Sign up to set email alerts
|

Projected Workforce of Psychiatrists in the United States: A Population Analysis

Abstract: Because of steady population growth and the retirement of more than half the current workforce, the psychiatrist workforce will continue to contract through 2024 if no interventions are implemented, leading to a significant shortage of psychiatrists. Despite an expected workforce expansion beginning in 2025, it is unclear whether the shortage will completely resolve by 2050. Future research should focus on developing strategies to address this quantified shortage in an effort to curb the worsening shortage thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 14 publications
(11 reference statements)
1
72
0
Order By: Relevance
“…There are too few physicians trained in treating substance use disorders to meet the demands of the current opioid epidemic in the United States —a symptom of the broader shortage of behavioral health clinicians. The US Department of Health and Human Services forecasts a national shortage of 6080–15 400 psychiatrists by 2025 .…”
mentioning
confidence: 99%
“…There are too few physicians trained in treating substance use disorders to meet the demands of the current opioid epidemic in the United States —a symptom of the broader shortage of behavioral health clinicians. The US Department of Health and Human Services forecasts a national shortage of 6080–15 400 psychiatrists by 2025 .…”
mentioning
confidence: 99%
“…Given the need for social isolation and fear of SARS-CoV-2, there is a worry that depressive symptoms and mental health challenges may increase, especially in vulnerable populations. 51,52 Finally, many people in need of mental health and substance use services are not identified as needing these services, [53][54][55][56][57][58] in part, due to lack of screening, human resource shortages, [59][60][61] fragmented and underfunded service delivery models, 62,63 and lack of youthfriendly services. 64 This issue is especially relevant in California where only *2% of young adults are engaged with community mental health programs, lower than the nationwide average.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different patterns of healthcare services utilization for each mental illness were not considered in the analysis, and changes in the population structure might not be consistent with the utilization patterns of patients. A study from the US [16], in which the population is predicted to increase in the future, indicated that a shortage of psychiatrists per population will occur despite the increasing number of psychiatrists. Apart from mental illness, Ishikawa and colleagues forecasted the distribution of physicians for patients with acute myocardial infarction, cerebral stroke, and all medical care in Hokkaido [5].…”
Section: Discussionmentioning
confidence: 99%